Kombinasi Senam Dysmenorrhea Dan Jus Wortel Efektif Menurunkan Nyeri Menstruasi Pada Remaja Putri - Machria Rachman; Maufirotul Jannah; Desi Trianita (Indonesian Journal of Midwifery Scientific, 2026)
Background: Lower abdominal pain during menstruation (dysmenorrhea) is commonly experienced by many adolescent girls, including female boarding school students. In East Java, the prevalence of primary dysmenorrhea is 71.3%. Complementary interventions to reduce menstrual pain include exercise and provision of carrot juice. This study aimed to determine the effect of dysmenorrhea exercise and carrot juice consumption on menstrual pain in adolescent females.. Methods: This study used a one-group pretest–posttest design. The population comprised all female students at Pondok Pesantren Annur Kalibaru Banyuwangi who experienced dysmenorrhea (43 individuals); a sample of 30 was selected by simple random sampling. Research instruments were a standard operating procedure (SOP) and an observation sheet using the Numerical Rating Scale. Statistical analysis was performed using the paired t-test. Results: Before the intervention, menstrual pain scores were moderate: scores 4 and 5 were each reported by 9 participants (30%). After the intervention, 19 participants (63.3%) reported mild pain. The paired t-test yielded a significance value of p = 0.000 (< 0.05), indicating that dysmenorrhea exercise combined with carrot juice significantly reduced menstrual pain. Conclusion: Support from educational and medical staff at the boarding school health post (Poskestren) should be optimized to identify dysmenorrhea early among adolescent female students. It is recommended to form adolescent groups to perform dysmenorrhea exercise three times per week for one week combined with consuming carrot juice twice daily. Keywords: dysmenorrhea exercise, carrot juice, menstrual pain, female boarding school students